Community Worldview of Springs in Panyabungan District - Torkis Lubis; Dede Hafirman Said; Hanifah Oktarina; Muhammad Ari Sahputra (Budapest International Research and Critics University, 2021)
Community behavior is basically a cultural manifestation that is influenced by several factors, including: environmental, social, economic and cultural conditions, as well as the behavior of people on the banks or around water sources in the Panyabungan sub-district. People use rivers and lakes as a means of bathing, washing and latrines. This behavior is a manifestation of culture caused by the functional relationship between humans and their environment. Bathing, washing, and latrine (MCK) is one of the needs of everyone. To meet these needs the community in the district. Panyabungan performs actions such as cleaning the body, washing clothes, household furniture and kitchen utensils as well as urinating and defecating, but there are some people who use water sources for business and excavation purposes. The purpose of this study was to determine the perception and attitude of the community regarding the springs, to determine the community factors in the use of water sources and the use of springs around us in daily life. Sampling was carried out in August 2021 using qualitative methods and data collection methods with interviews using questionnaires. The results showed that most of the people in the district. Panyabungan utilizes water sources and springs for bathing, washing, latrine activities as well as businesses such as excavation C and drinking water companies. This is caused by several factors, including environmental, social, economic and cultural conditions. Public understanding of clean and healthy behavior is quite high, although the manifestation of behavior in utilizing river water, lakes as a means of bathing and washing in fulfilling other needs is still carried out. Meanwhile, for food and drinking needs, in general, they still use drilled wells and PDAM water. From the results of this study, no significant health impact was found, instead what was felt was that the environment seemed shabby, clothes that were washed easily faded and became wrinkled.